98.0k views
4 votes
when solving the system below algebraically using the substitution method, which of the following could be an equation you could. create to solve for x?A) x = 3y - 3B) -2x + 6(2x + 11) = 6C) -2x - 6 = - 2x - 11D) -2 (3y - 3) + y = 11

when solving the system below algebraically using the substitution method, which of-example-1
User Grandia
by
5.4k points

1 Answer

5 votes

We have that the solutions of the system are


x\text{ = -6 and y = -1}

So we are going to check which of the answers give that answer, we are going to try with A fisrt


x\text{ = }3(-1)\text{ }-3\text{ = -6}

So with A, the solutions are the same, so we have that the answer is A.

User Kinkajou
by
5.1k points